Reflections on the Collaborative Fight Against COVID-19 - Goldman, Michel; Silva, Mitchell (Frontiers in Medicine, 2020)
Clinical trials to identify efficient treatments against COVID-19 flourish worldwide without much attention to patients' voice so far. As therapeutic interventions in the early phase of the disease are attracting more and more interest, we argue that now is the time to involve patients' organizations in the design of clinical protocols in order to define the most relevant end-points and assess the risk-benefit balance of new therapies.